2021
DOI: 10.1097/cin.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning–Based Fall Risk Assessment Model for Inpatients

Abstract: Falls are one of the most common accidents among inpatients and may result in extended hospitalization and increased medical costs. Constructing a highly accurate fall prediction model could effectively reduce the rate of patient falls, further reducing unnecessary medical costs and patient injury. This study applied data mining techniques on a hospital's electronic medical records database comprising a nursing information system to construct inpatient-fall-prediction models for use during various stages of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
3
12
1
1
Order By: Relevance
“…Patients in this study who experienced falls tended to be older, stayed in the hospital longer, and took more medications. This result is consistent with the characteristics of patients at risk for falls, as in previous studies 14,18 . All these characteristics were used as significant predictors.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Patients in this study who experienced falls tended to be older, stayed in the hospital longer, and took more medications. This result is consistent with the characteristics of patients at risk for falls, as in previous studies 14,18 . All these characteristics were used as significant predictors.…”
Section: Discussionsupporting
confidence: 93%
“…Medication and nursing intervention was important predictors consistent with previous study 18 . Lower limb weakness and dysuria was the highest predictor in previous study 14,22 , assist toileting and ambulation nursing interventions were found to be high predictor, which was similarly consistent. Another study shows admission data was high in feature importance, but this study inputted more variables to reflect specific patient conditions.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…With advancing technology and improved medical informatics, some researchers predicted falls in hospitalized patients based on electronic health records (EHR), but data from HER also have some limitations (30,31). Since many risk factors have been found and the evolution of computer science and artificial intelligence, many scientists would like to predict falls by means of machine learning (32)(33)(34)(35) (Table 1). However, most datasets consisted of relatively healthy people, or young people (36).…”
Section: Introductionmentioning
confidence: 99%